2021
DOI: 10.1177/2167702621989665
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personality Pathology Across Three Generations: Evidence From the St. Louis Personality and Intergenerational Network Study

Abstract: Personality disorder (PD) symptoms in a parent generation may confer risk for problems in future generations, but intergenerational transmission has not been studied beyond parent–child effects. We examined the generational transfer of risk associated with PDs using structural models of grandparent personality pathology and grandchild psychopathology among 180 adults (mean age = 66.9 years), 218 of their children (mean age = 41.2 years), and 337 of their grandchildren (mean age = 10.5 years). We found evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…For our key coefficients to be more meaningful and comparable with the literature (Corthorn, 2018; Rivas et al, 2020; Shields et al, 2021; Thompson et al, 2021; Vuorre et al, 2021), we standardized the IRT scores with respect to the IRT scores in the study’s first wave of data collection. Hence, all standardized scores have an average equal to zero and a standard deviation equal to one in Wave 1.…”
Section: Methodsmentioning
confidence: 99%
“…For our key coefficients to be more meaningful and comparable with the literature (Corthorn, 2018; Rivas et al, 2020; Shields et al, 2021; Thompson et al, 2021; Vuorre et al, 2021), we standardized the IRT scores with respect to the IRT scores in the study’s first wave of data collection. Hence, all standardized scores have an average equal to zero and a standard deviation equal to one in Wave 1.…”
Section: Methodsmentioning
confidence: 99%
“…The personality traits of children are influenced by those of their parents according to intergenerational transmission of the personality. 59 Numerous studies have concluded that the emergence of Dark Triad in children is associated with dark personality traits such as parental indifference and control during childhood, with such influences persisting. 60 That is, the higher the level of parental Dark Triad, the more likely that their children will develop Dark Triad.…”
Section: Introductionmentioning
confidence: 99%